2012
DOI: 10.1111/j.1469-0691.2011.03697.x
|View full text |Cite
|
Sign up to set email alerts
|

The incidence and risk factors of invasive fungal infection after haploidentical haematopoietic stem cell transplantation without in vitro T-cell depletion

Abstract: Clin Microbiol Infect 2012; 18: 997–1003 Abstract In recent years, we have successfully established a novel method of haploidentical haematopoietic stem cell transplantation (HSCT) without in vitro T‐cell depletion. This study was aimed at analysing the incidence and risk factors of invasive fungal infection (IFI) with this transplantation method. The study comprised 291 patients who had undergone haploidentical HSCT from 1 January 2007 to 31 December 2008. IFI was diagnosed according to the European Organizat… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

3
25
1
1

Year Published

2012
2012
2023
2023

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 29 publications
(30 citation statements)
references
References 21 publications
3
25
1
1
Order By: Relevance
“…The immune reconstitution following unmanipulated HBMT has been recently reviewed elsewhere [32]; here we focus on IFI and CMV infection. The incidence rates of IFI in patients with zero, one, two, or three risk factors 3 years after transplantation were 4.48, 7.86, 29.6, and 23.1%, respectively [28]. The cumulative incidences of IFI at 40 days, 1 year, 2 years, and 3 years after transplantation were 8.25, 13.1, 13.4, and 13.4%, respectively.…”
Section: Immune Recovery and Infections After Haploidentical Blood Anmentioning
confidence: 92%
See 1 more Smart Citation
“…The immune reconstitution following unmanipulated HBMT has been recently reviewed elsewhere [32]; here we focus on IFI and CMV infection. The incidence rates of IFI in patients with zero, one, two, or three risk factors 3 years after transplantation were 4.48, 7.86, 29.6, and 23.1%, respectively [28]. The cumulative incidences of IFI at 40 days, 1 year, 2 years, and 3 years after transplantation were 8.25, 13.1, 13.4, and 13.4%, respectively.…”
Section: Immune Recovery and Infections After Haploidentical Blood Anmentioning
confidence: 92%
“…Over the past several years, results of unmanipulated HBMT have substantially improved due to enhanced GVHD prophylaxis [4], insight into immune reconstitution and infections [25][26][27][28][29], novel strategy for relapse prophylaxis and treatment [30,31 && ], and improved supportive care strategies.…”
Section: Current Status Of Unmanipulated Haploidentical Blood and Marmentioning
confidence: 99%
“…However, recent epidemiological studies in China have shown that the incidence of IFDs is increasing due to the increase in hematopoietic malignancies as well as the wide development of allo-HSCTs (14,15). The incidence of IFDs after haploidentical stem cell transplantation is significantly higher than that after HLA-matched sibling transplantation (2); Aspergillus is the most common pathogenic species of IFD in Chinese patients undergoing allo-HSCT (3). Patients with aGVHD and cGVHD, and elderly patients were reported to be at higher risk for fungal infections (16).…”
Section: Discussionmentioning
confidence: 99%
“…Invasive fungal disease (IFD) remains a major cause of morbidity and mortality after allogeneic hematopoietic stem cell transplantation (allo-HSCT) (1); aspergillosis is the most common IFD infection among HSCT recipients (2,3). The most common form of disease due to Aspergillus species in immunocompromised patients is invasive pulmonary aspergillosis (IPA), which mainly involves the lung parenchyma (4), the development of invasive tracheobronchial aspergillosis (ITBA) and invasive laryngeal aspergillosis is rare; however, the development of fulminant ITBA is associated with a serious prognosis (5,6).…”
Section: Introductionmentioning
confidence: 99%
“…Currently, IFIs constitute a clinical issue on the rise in the ICUs both in the developing and developed world [19,20] . Predisposing factors such as patients' complicated medical or surgical status, invasive bedside procedure and wide administration of antibiotics have contributed to increased rate of IFIs, mainly IC and invasive aspergillosis (IA), in the ICU [21][22][23] . Candidemia is thus far known to be the most prevalent fungal infection afflicting ICU patients [23] .…”
Section: Problem On the Risementioning
confidence: 99%